Evolution of the temporal structure of world high competition judo combat (2013 a 2017) - Fernandes Monteiro, L.; Gonçalves, J.; Chambel, L.; Abel, M. (Revista de Artes Marciales Asiaticas, 2019)
Judo is a sport that is constantly evolving. Rule modifications and changes in tactical strategies have enhanced scoring opportunities and reduced penalties. This study analyzed the evolution of the temporal structure of combat through an assessment of the total match time (TMT), time engaged in combat (CT), time without (TWOG) and with grip (TWG), pause time (PT), the percentage of combat time in tachi-waza and combat in ne-waza, and the frequency of combat/tactical/technical actions/tasks. Data were descriptively analyzed overtime during the 2013, 2014, 2015, and 2017 World Championships and the 2016 Olympic Games. Data from 3,084 male and female matches across weight and gender categories were collapsed and used to compare the TMT, CT, TWOG, TWG, PT, and frequency of tactical actions over time and by competition phase (i.e., qualifiers, quarterfinals, recaps, semi-finals, bronze and finals). There were several temporal changes that occurred due to the rules modifications. The TMT increased by 3.6% over the sampling period for all competition phases. Regarding the duration of combat activities, relative to TMT: 25% was spent in PT (M PT = 8.9 s); 36% (M TWG = 9.6 s) was spent in TWG; 25% (M = 7.3 s) was spent in TWOG; 15% was spent in ne-waza (M = 7.7 s per action). With the changes of the rules in 2017, there was a Golden Point Score increase of 25% in the total number of combat; in relation to the competition phase, there was a 50% increase in the total number of combat activities. There was also a 15% increase in the number of actions in the competition final phase. There was some variation of the time structure of the combat, namely in the total time of the fighting and Golden Point, as a consequence of the change of the Referee rule changes.